Simultaneous integrated boost with intensity modulated radiation therapy in brain oligometastases: A feasible technique for developing countries - Tiwari, Vivek (South Asian J Cancer, 2015)
INTRODUCTION: To analyze the pattern of brain metastasis (BM), and to use intensity modulated radiation therapy (IMRT) for target dose escalation in cases with ≤3 metastatic lesions (oligometastases). MATERIALS AND METHODS: Thirty-two consecutive cases of BM treated during September 2009 to August 2012 were analyzed retrospectively. RESULTS: The study comprised 13 males (40.62%) and 19 females (59.37%). Thirteen (40%) patients presented with disseminated intracranial metastases, while 19 (60%) had ≤3 foci. In 25 cases (78%), the primary was located either in the breast (14 cases) or lung (11 cases). The 13 patients with disseminated intracranial metastases received whole brain radiation therapy to a dose of 30 Gy/10-12 daily fractions (Group A) while the 19 cases with ≤3 lesions received an additional dose of 6-10 Gy to gross lesions using a simultaneous integrated boost (SIB) with IMRT thus receiving a total dose of 36-40 Gy/12-15 fractions (Group B). Overall survival (OS) for the breast primary was 6.3 and lung primary was 5.3 months, respectively. The mean OS for breast cases in Group B was higher (9.5 months) as compared to Group A cases (1.9 months) and was statistically significant (P = 0.0056). Similarly, primary lung cancer cases in Group B showed a mean OS of 8.75 months versus 2.6 months for Group A cases (P = 0.213). CONCLUSIONS: IMRT is a safe and effective technique in cases with oligometastases for dose escalation in the form of SIB.